Associations of mediterranean diet score and age-related macular degeneration in Korean elderly - Won Jang; Jungeun Choi; Hyesook Kim (BMC, 2024)
Abstract Background Previous studies have reported associations between individual nutrients or specific foods and the risk of age-related macular degeneration (AMD). However, the relationship between overall dietary quality, specifically the alternative Mediterranean diet (aMED) score, and AMD remains unclear. Therefore, this study aimed to investigate the association between the aMED score, as an indicator of overall diet quality, and AMD in the Korean population. Methods We conducted a cross-sectional analysis using nationally representative samples of older adults aged ≥ 65 years (895 men and 1,191 women) from the Korea National Health and Nutrition Examination Survey (2017-2018). Food intake and the aMED score were estimated using 24-h recall. AMD was diagnosed by an ophthalmologist based on fundus photography. The associations of aMED score tertiles with AMD were determined using odds ratios (ORs) from multivariate logistic regressions. Results Multiple logistic regression analysis revealed a significantly negative association between the aMED score and AMD (adjusted ORs = 0.58; 95% confidence interval = 0.39-0.88; p-trend = 0.021) in older men after adjusting for confounding factors such as age, body mass index, family monthly income, current smoking, alcohol consumption, physical activity, chronic disease status, and energy intake. Notably, this association was exclusively observed in men, and no significant association was observed between the aMED score and AMD in women (adjusted OR = 0.88; 95% CI = 0.61-1.29; p-trend = 0.691). Conclusions This study's findings suggest that a high aMED score may be associated with a reduced risk of AMD in older men. Future studies with larger sample sizes and a prospective or interventional design are required to enhance current understanding regarding the association between diet quality and AMD.